Robust Optimal Planning and Operation of Electrical Energy Systems - Mohammadi-ivatloo, Behnam; Nazari-Heris, Morteza; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the recent developments in robust optimization (RO) and information gap design theory (IGDT) methods and their application for the optimal planning and operation of electric energy systems. Chapters cover both theoretical background and applications to address common uncertainty factors such as load variation, power market price, and power generation of renewable energy sources. Case studies with real-world applications are included to help undergraduate and graduate students, researchers and engineers solve robust power and energy optimization problems and provide effective and promising solutions for the robust planning and operation of electric energy systems.
Optimal planning issues of electric energy systems under uncertainty -- Optimal operation issues of electric energy systems under uncertainty -- Introduction to robust optimization (RO) method -- Introduction to information gap decision theory (IGDT) method -- Robust optimal planning and operation of electric energy systems -- Robs unit commitment -- Robust short-term scheduling -- Robust optimal power flow -- Robust transmission network expansion planning -- Robust strategic bidding of energy management systems -- Robust energy generation scheduling -- Robust economic dispatch problem in renewable-based hybrid energy systems -- Robust electricity market optimization -- Robust optimal design of hybrid energy systems.
Keywords: Electric power production; Renewable energy sources; Electrical Power Engineering; Renewable Energy; Mechanical Power Engineering